أثر الهندسة النفسية والبرمجة اللغوية العصبية (NLP) على جودة التدقيق الداخلي (دراسة استطلاعية): The impact of psychological engineering and neuro-linguistic programming (NLP) on the quality of internal audit - خالد عبيد احمد العبيدي; قرارة سامية (Journal of North African Economies, 2025)
The research aims to identify the concepts, foundations and objectives of psychoengineering and neuro-linguistic programming (NLP), analyze the impact of psychoengineering and neuro-linguistic programming (NLP) on the quality of internal auditing, upgrade the performance of internal auditors, and reach results that help us build a set of recommendations for decision makers. The importance of research in investing the psychoengineering system to improve the quality of internal auditing was highlighted, and the analytical descriptive curriculum was followed. The research sought to test the extent to which the visual, sensory and auditory pattern had an impact on the quality of internal auditing, as well as to demonstrate the impact of psychoengineering and neurolinguistic programming (NLP) on the quality of internal auditing. We have come to the conclusion that neuro-linguistic programming plays a role in enhancing the quality of internal auditing by activating its assumptions among internal auditors, which will change results and bring them to outstanding performance.